2015
DOI: 10.1021/acsnano.5b00896
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Topological Surface State on the Thermoelectric Transport in Sb2Te3 Thin Films

Abstract: Ab initio electronic structure calculations based on density functional theory and tight-binding methods for the thermoelectric properties of ptype Sb 2 Te 3 films are presented. The thicknessdependent electrical conductivity and the thermopower are computed in the diffusive limit of transport based on the Boltzmann equation. Contributions of the bulk and the surface to the transport coefficients are separated which enables to identify a clear impact of the topological surface state on the thermoelectric prope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 37 publications
3
44
0
Order By: Relevance
“…To consider a two-band model of a TI, the total thermopower and electrical conductivity come from the surface state and the bulk carriers. The total electrical conductivity is expressible as σ total  =  σ bulk  +  σ surface ; the total thermopower is expressed as S total  = ( σ bulk S bulk  +  σ surface S surface )/ σ total 26. In a thin-film system, the contribution of electrical conductivity from bulk bands can be decreased on controlling the thickness of the TI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To consider a two-band model of a TI, the total thermopower and electrical conductivity come from the surface state and the bulk carriers. The total electrical conductivity is expressible as σ total  =  σ bulk  +  σ surface ; the total thermopower is expressed as S total  = ( σ bulk S bulk  +  σ surface S surface )/ σ total 26. In a thin-film system, the contribution of electrical conductivity from bulk bands can be decreased on controlling the thickness of the TI.…”
Section: Resultsmentioning
confidence: 99%
“…In early work, Hicks and Dresselhaus proposed that low-dimensional systems could enhance the thermoelectric efficiency through an enlarged thermopower22, but a decreased thermopower value was observed in Sb 2 Te 3 thin films; the discrepancy was resolved in recent work on Sb 2 Te 3 thin films232425. The separate contributions to thermopower from the bulk and the surface could cause a decreased total thermopower26. A surface state existing in the energy gap with a small concentration of bulk carriers could benefit an enhanced thermopower.…”
mentioning
confidence: 99%
“…Instead, it exhibits a peculiar sign anomaly with the Hall effect induced by the drastically different transport properties of the bulk and surface states [12]. In a more recent study of p-type Sb 2 Te 3 TI thin films [13], it was found that tuning the E F position and film thickness has a significant impact on the total thermopower, also demonstrating the effect of topological surface states on the thermoelectric properties of TI.…”
Section: Introductionmentioning
confidence: 99%
“…The observed TE properties of pure m-TSDS allows us to discuss the accuracy of theoretical predictions. TE properties of 3D-TIs are mainly discussed in the framework of a semi-classical Boltzmann transport equation (SBTE) [19][20][21][22][23][24][25] . For the conventional materials, the physical parameters required for comparing the experimental data to the theoretical calculations are the chemical potential μ and relaxation time τ.…”
mentioning
confidence: 99%